Cooperation and Punishment in Public Goods Experiments - Ernst Fehr; Simon Gaechter (Center for Economic Studies and ifo Institute (CESifo), 1999)
This paper provides evidence that free riders are heavily punished even if punishment is costly and does not provide any material benefits for the punisher. The more free riders negatively deviate from the group standard the more they are punished. As a consequence, the existence of an opportunity for costly punishment causes a large increase in cooperation levels because potential free riders face a credible threat. We show, in particular, that in the presence of a costly punishment opportunity almost complete cooperation can be achieved and maintained although, under the standard assumptions of rationality and selfishness, there should be no cooperation at all. We also show that free riding causes strong negative emotions among cooperators. The intensity of these emotions is the stronger the more the free riders deviate from the group standard. Our results provide, therefore, support for the hypothesis that emotions are guarantors of credible threats.
Keywords: 330; Voluntary cooperation; public good; punishment; emotions; social norms; experiments